ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU PADA PENGOLAHAN KERUPUK MIKONG DI HOME INDUSTRY KAMPUNG SURYA BAKI KOTA SUMBAWA BESAR MENGGUNAKAN METODE ECONOMIC ORDER QUANTITY (EOQ) - ulfaturrahmi ulfa; Dinda Permata; Titin Asmawati; Dwita Haerani (Hexagon, 2025)
ABSTRACT The purpose of this research is to analyze the control of raw cowhide inventory carried out by the home industry "Kerupuk Mikong Khas Sumbawa," to analyze the control of raw cowhide inventory in the home industry "Kerupuk Mikong Khas Sumbawa" using the Economic Order Quantity (EOQ) method, to compare the total inventory cost using the EOQ method with the total inventory cost calculated conventionally in the home industry "Kerupuk Mikong Khas Sumbawa," and to propose improvements to the total inventory cost incurred by the home industry "Kerupuk Mikong Khas Sumbawa.". The method used in this study is the Economic Order Quantity (EOQ) method. The results of this research show that the control of raw cowhide inventory using the EOQ method yields an optimal order quantity of 6,544 kilograms, with an ordering frequency of 19 times per year. The ordering cost is IDR 94,850 per year, the holding cost is IDR 94,888 per year, the safety stock is 288 kilograms per year, and the reorder point (ROP) is 688 kilograms. The comparison of total inventory costs using the EOQ method and conventional inventory cost calculation reveals a reduction in inventory costs when using the EOQ method. This is due to a decrease in the ordering frequency from 48 times to 19 times, reducing the ordering cost from IDR 240,000 per year to IDR 94,850. Additionally, the holding cost decreases from IDR 3,600,000 to IDR 94,888 per year, with the total inventory cost dropping from IDR 3,602,040 to IDR. Keywords: Raw Material, Economic Order Quantity (EOQ), Home Industry “Kerupuk Mikong Khas Sumbawa”.